Labour and Labour Welfare Schemes in the Third Five Year Plan - Planning Commission, Government of India (Planning Commission, Government of India, 1961)
This document provides a detailed account of labour and labour welfare programmes under India’s Third Five Year Plan (1961–1966), outlining both Central and State initiatives designed to strengthen employment generation, skill development, and worker welfare across the country. It systematically presents financial allocations, physical targets, and phased expenditures, enabling implementing agencies to effectively plan and execute schemes over the five-year period. Key focus areas include craftsmen training, employment services, expansion of Employees’ State Insurance, labour welfare administration, and the development of institutional support systems such as training centres, labour research units, and statistical frameworks. The plan emphasises manpower development through technical education and vocational training, aiming to align workforce skills with the needs of a growing economy. It also incorporates measures for social security, including relief funds for retrenched workers and assistance for vulnerable groups. By providing state-wise and sector-wise breakdowns, the document highlights regional variations and the coordinated role of central and state governments in implementing labour policies. Overall, the plan reflects a comprehensive approach to improving labour conditions, enhancing productivity, and promoting equitable economic development through structured investment in human resources and welfare mechanisms.
Planning Commission, Labour and Employment Division, Government of India
Planning Commission, Labour and Employment Division, Government of India
Keywords: Third Five Year Plan- Labour and Labour Welfare Schemes; Labour Welfare, Employment Services; Labour Statistics